Paternalistic Leadership and Psychological Well-Being: The Mediating Role of Meaningful Work - (:unkn) unknown (My University, 2017)
This article probes into the meaningfulness of work as a potential mediator betweenpaternalistic leadership and well-being as well as an outcome, being one of the dimensions of psychological empowerment. This is addressed in this preparatory study. According to hypothesis, leadership behavior, ahead of that of other influential variables,can contribute to the prediction of psychologic well-being at work. In order to measurepaternalistic leadership behaviour, we have used a questionnaire-based instrument whosevalidity and reliability of the instrument have already been proven by Aycan in Turkey.The research hypothesis was tested using single and multiple regression by the mediating model of Baron and Kenny within a convenience sample consisting of 77 males andfemales working in a variety of organizations, occupations, and industries in Turkey. Theresults of the analyses conducted have revealed that benevolent paternalistic leadershipand executive/authorized paternalistic leadership factors have significant effects on positive effect and negative effect factors of well-being construct and the work meaningfulness variable has a mediating role on these effects. In addition, it has been exhibited thatexecutive/authorized benevolent leadership has a significant effect on fulfillment factorof well-being construct and the variable work meaningfulness has a mediating role onthis effect. Additional evidence is provided herein, with respect to the fact that leadershipbehaviour can affect employee well-being and it is suggested that the individuals thatseek creating healthier workplaces should not neglect supervision. It is argued that, for those concerned with psychosocial working conditions, it is now sufficiently justifiableto consider supervisor behaviour as a potentially influential variable. Moreover, a newmodel is presented in the study for assessing the supervisor behavior with the potentialvalue for the future studies.

Bu makale, paternalist liderlik ile psikolojik iyi olma durumu arasında potansiyel bir arabulucu olarak, psikolojik güçlenmenin boyutlarından biri olan iş anlamlılığını analiz etmektedir. Çalışmada belirlenen hipoteze göre, liderlik davranışı, diğer etkili değişkenlerin ötesinde, işyerinde psikolojik refahın tatmini için katkıda bulunabilir. Babacan liderlik davranışını ölçmek için, “Aycan” tarafından Türkiye’de geçerliliğini ve güvenilirliğini ispatlamış olan bir ölçek kullanılmıştır. Araştırma hipotezi tek ve çoklu regresyon kullanılarak Baron ve Kenny aracı etki modeliyle test edilmiştir. Türkiye’de çeşitli organizasyonlar, meslekler ve endüstrilerde çalışan 77 erkek ve kadın araştırmanın örneklemini oluşturmaktadır. Yapılan analizler sonucunda; iyiliksever babacan liderlik ve icracı/yetkili babacan liderlik faktörlerinin, iyi olma yapısının altında yer alan pozitif etki ve negatif etki boyutları üzerinde anlamlı etkilere sahip olduğu ve işin anlamlılığı değişkeninin bu etkiler üzerinde kısmi aracılık rolünün bulunduğu belirlenmiştir. Ayrıca; icracı/yetkili babacan liderliğin, iyi olma yapısının altında yer alan gerçekleşme boyutu üzerinde anlamlı bir etkiye sahip olduğu ve işin anlamlılığı değişkeninin bu etki üzerinde tam aracılık rolünün bulunduğu belirlenmiştir. Araştırma sonuçları, liderlik davranışının çalışanların refahını etkileyebileceği ve sağlıklı işyeri yaratmaya çalışan kişilerin bunu göz ardı etmemesi gerektiği konusunda ilave kanıtlar sağlamaktadır. Psikososyal çalışma koşullarıyla ilgilenen kişiler için yöneticilerin davranışlarını, çalışanlar üzerinde etkili bir değişken olarak ele almak gerekebilir. Bu çerçevede, gelecekteki çalışmalar için önemli bir potansiyele sahip olan yöneticilerin davranışını değerlendirmek için yeni bir model sunulmaktadır.
Babacan Liderliğin Psikolojik İyi Olmaya Etkisinde İşin Anlamlılığının Aracılık Rolü
Keywords: Tarih